Gut bacteria interact directly with colonic mast cells in a humanized mouse model of IBS - Chiko Shimbori; Giada De Palma; Lauren Baerg; Jun Lu; Elena F. Verdu; David E. Reed; Stephen Vanner; Stephen M. Collins; Premysl Bercik (Gut Microbes)
Both mast cells and microbiota play important roles in the pathogenesis of Irritable Bowel Syndrome (IBS), however the precise mechanisms are unknown. Using microbiota-humanized IBS mouse model, we show that colonic mast cells and mast cells co-localized with neurons were higher in mice colonized with IBS microbiota compared with those with healthy control (HC) microbiota. In situ hybridization showed presence of IBS, but not control microbiota, in the lamina propria and RNAscope demonstrated frequent co-localization of IBS bacteria and mast cells. TLR4 and H4 receptor expression was higher in mice with IBS microbiota, and in peritoneal-derived and bone marrow-derived mast cells (BMMCs) stimulated with IBS bacterial supernatant, which also increased BMMCs degranulation, chemotaxis, adherence and histamine release. While both TLR4 and H4 receptor inhibitors prevented BMMCs degranulation, only the latter attenuated their chemotaxis. We provide novel insights into the mechanisms, which contribute to gut dysfunction and visceral hypersensitivity in IBS.